SUPERCRITICAL EXTRACTION OF CARYOPHYLLENE FROM MELALEUCA CAJUPUTI LEAVES AS PADDY HERBICIDES ALLELOPATHY: OPTIMIZATION, MODELLING AND EFFICACY TEST - BENJAMIN , KUEH WEI BIN (2018)
In light of rice production problem and food security, control of paddy weeds with incorporation of allelopathy compounds served as new alternative for sustainable weeds management. In current studies, the oil from Melaleuca cajuputi was extracted and analyzed for its possible allelopathy compound present. Central composite design (CCD) was used to optimize the oil yield of Melaleuca cajuputi leaves using supercritical carbon dioxide (SC-CO2) extraction.